Compututor video DOS - Harvey, Jackson; Lynch, Timothy (Computer video training course, 1986)
An introduction to the main features of the disk operating system for the IBM PC and compatibles. The program is designed for users of PC DOS 2.1 or higher and includes segments on batch files and subdirectories as well as more basic aspects.